The Faith of a Physicist : Reflections of a Bottom-Up Thinker. - Polkinghorne, John C. (Princeton legacy library., 2014)
Is it possible to think like a scientist and yet have the faith of a Christian? Although many Westerners might say no, there are also many critically minded individuals who entertain what John Polkinghorne calls a ""wistful wariness"" toward religion--they feel unable to accept religion on rational grounds yet cannot dismiss it completely. Polkinghorne, both a particle physicist and Anglican priest, here explores just what rational grounds there could be for Christian beliefs, maintaining that the quest for motivated understanding is a concern shared by scientists and religious thinkers ali